Low temperature EPR investigation of Co2+ ion doped into rutile TiO2 single crystal: Experiments and simulations - (:unkn) unknown (ELSEVIER SCIENCE BV, 2017)
In this paper, we present the results of X-band EPR spectra of Co2+ ion doped rutile (TiO2) which is one of the most promising memristor material. We obtained the angular variation of spectra in three mutually perpendicular planes at liquid helium (7-13 K) temperatures. Since the impurity ions have 1/2 effective spin and 7/2 nuclear spin, a relatively simple spin Hamiltonian containing only electronic Zeeman and hyperfine terms was utilized. Two different methods were used in theoretical analysis. Firstly, a linear regression analysis of spectra based on perturbation theory was studied. However, this approach is not sufficient for analyzing Co+2 spectra and leads to complex eigenvectors for G and A tensors due to large anisotropy of eigenvalues. Therefore, all spectra were analyzed again with exact diagonalization of spin Hamiltonian and the high accuracy eigenvalues and eigenvectors of G and A tensors were obtained by taking into account the effect of small sample misalignment from the exact crystallographic planes due to experimental conditions. Our results show that eigen-axes of g and A tensors are parallel to crystallographic directions. Hence, our EPR experiments proves that Co2+ ions substitute for Ti4+ ions in lattice. The obtained principal values of g tensor are g(x)=2.110(6), g(y)=5.890(2), g(z)=3.725(7) and principal values of hyperfine tensor are A(x)=42.4, A(y)=152.7, A(z)=26 (in 10(-4)/cm).
Keywords: Co2+; TiO2; Rutile; EPR, low temperature; PARAMAGNETIC-RESONANCE; THIN-FILMS; FERROMAGNETISM